Morphosyntactic in Children with Development Language Disorder : A Systematic Review - Kiyat Sudrajad; Windiarti Dwi Purnaningrum (Jurnal Terapi Wicara dan Bahasa, 2026)
Background: Morphosyntax refers to language structure encompassing both morphology and syntax as a unified organization; these two fields are inseparable. Morphology and syntax constitute a single, indivisible component. Child language acquisition is closely linked to social communication; children engage in social communication from birth, and their language development depends on their social environment (Feldman, 2019). Specific Language Impairment (SLI) is a condition wherein verbal development disorders are diagnosed when children fail to acquire language without an apparent cause (Bishop, Snowling, Thompson, & Greenhalgh, 2016). Objectives: To analyze the morphosyntactic abilities of children with Developmental Language Disorder (DLD) and to provide additional information on this subject. Methods: This study is a systematic review utilizing data from previous research. A quantitative systematic review aggregates findings from various independent studies to produce a statistical summary of those findings (Last, 2001, cited in Murti, 2018). Results: Preschool children with DLD can demonstrate significant improvement in morphosyntactic skills. Conclusion: While an improvement in morphosyntactic skills was observed during the intervention period, it could not be definitively attributed to the intervention itself, as both target structures and control structures showed improvement during that time. Keywords: Morphosyntactic, DLD, Systematic Review.